Two kinds of Airy-related beams. (13th July 2015) - Xu, Yiqing; Zhou, Guoquan; Zhang, Lijun; Ru, Guoyun
Abstract: Two kinds of Airy-related beams are introduced in this manuscript. The normalized intensity distribution in the x -direction of the two kinds of Airy-related beams is close to that of the Gaussian beam. The normalized intensity distribution in the y -direction of the two kinds of Airy-related beams is close to that of the second-order and the third-order elegant Hermite–Gaussian beams, respectively. Analytical expressions of the two kinds of Airy-related beams passing through an ABCD paraxial optical system are derived. The beam propagation factors for the two kinds of Airy-related beams are 1.933 and 2.125, respectively. Analytical expressions of the beam half widths and the kurtosis parameters of the two kinds of Airy-related beams passing through an ABCD paraxial optical system are also presented. As a numerical example, the propagation properties of the two kinds of Airy-related beams are demonstrated in free space. Moreover, the comparison between the two kinds of Airy-related beams and their corresponding elegant Hermite–Gaussian beams along the two transverse directions are performed in detail. Upon propagation, the former kind of Airy-related beam will evolve from the central bright beam into the dark hollow beam. Contrarily, the latter kind of Airy-related beam will evolve from the dark hollow beam into the central bright beam. These two kinds of Airy-related beams can be used to describe specially distributed beams.